Assume the Position: Exploring Discipline Relationships - Travis, Melissa E (2013)
Discipline relationships are consensual adult relationships between submissive and dominant partners who employ authority and corporal punishment. This population uses social media to discuss the private nature of their ritualized fantasies, desires, and practices. Participants of these relationships resist a sadomasochistic label of BDSM or domestic abuse. I conducted in-depth interviews and narrative analysis of social media to explore experiences and identities of people in discipline relationships. The sample includes social media bloggers and past and present participants in discipline relationships. I compared explanations participants give for wanting and participating in discipline relationships. I combine identity theory, constructionism, post-structuralism, and critical feminism as an analytic frame to understand this practice sociologically. I found gender differences in the media format and communication style of participants, but the ritualized expressions for discipline relationships remain consistent regardless of gender. The social process of community identification for participants includes coming out, educating others and “inviting in.” The online community provides a forum for relationship negotiation techniques, and encouraging the embrace of non-normative sexual identity. Participants use social media to form a nascent social movement that resists normative views of sexuality and relationships in the dominant culture